Kewenangan Uji Material (Judicial Review) Ketetapan Majelis Permusyawaratan Rakyat oleh Mahkamah Konstitusi - Pratiwi, Lintang Galih (SASI, 2020)
The re-enters of People’s Consultative Assembly’s Provision (MPR’S Provision) in the regulations of law hierarchy in Indonesia legal system, certainly has its own impact. One of them is the authority of the Constitutional Court in conducting judicial review. The problem is whether the Constitutional Court can review the MPR’S Provision or not. The research method used in this research was normative-juridical method. The research finding shows that: first, the Constitutional Court in its verdict stated that it has no power to be competent to review the MPR’S Provision. Second, the implication of that verdict is the causing the legal vacuum and the absence of the institution that is authorized to do a trial towards the MPR’s provisions. Third, to answer that problem, MPR’S Provision should be equalized with the Law (Act), so the authority to review People’s Consultative Assembly’s adjudication belongs to the Constitutional Court.